Analysis of the Implementation of the Integrated Industrial Area Development Policy for Tukak Sadai Port in South Bangka Regency, Bangka Belitung Islands Province. - Muhammad Afdhal Abdiansyah; Dea Melati; Muhamad Anang Munawir (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
South Bangka Regency sits near Indonesia’s Archipelagic Sea Lane (ALKI 1), giving Tukak Sadai Port the potential to anchor a port-based integrated industrial zone and stimulate local competitiveness. Yet a policy gap across central, provincial, and district levels has raised concerns about whether the program is being implemented effectively. This study aims to explain why implementation of the Tukak Sadai Port Integrated Industrial Area (KIT) remains suboptimal, using Grindle’s policy implementation framework (policy content and implementation context) as the main analytical lens. A qualitative descriptive design was employed, drawing on interviews, field notes, and official documents, and analyzing data by matching empirical patterns with the theoretical indicators. Findings show that implementation has progressed and produced local multiplier effects (infrastructure expansion, MSME development, commodity absorption, and job creation), and the project has entered Phase II aligned with the spatial plan (RTRW). However, coordination among regional apparatus organizations and partners is uneven, several supporting studies have not been completed, and governance arrangements with the area manager (PT RBA) require clearer oversight and evaluation. The study recommends establishing a Bappeda-led coordination team and issuing district-level regulations to strengthen legal certainty, accountability, and inter-agency synchronization.